Fala espontânea e gesto: um estudo qualitativo baseado em corpus - Marianna Bicalho de Albuquerque (2025)
The aim of this study, focused on the analysis of spontaneous speech, was to examine the gestures produced alongside phenomena such as disfluencies, rhetorical scansions, and the informational units of multiple comments, topics, and locutive introducers. In this context, gestures are understood as deliberate actions that serve expressiveness (Kendon, 2004; McNeill; Duncan, 2000). Studies based on corpora and grounded in the Language into Act Theory (Cresti, 2000; Moneglia; Raso, 2014; Cavalcante, 2020), the main theoretical framework underpinning this research, have shown that the boundary zones of gestural units tend to coincide with the prosodic boundaries of speech (Cantalini, 2018; Cantalini; Moneglia, 2020; Barros, 2021; Bicalho, 2023). This research was developed using a spontaneous speech corpus, C-ORAL-BGEST (Mello et al., 2024), informationally annotated according to the Language into Act Theory and gesturally annotated following the guidelines of McNeill (1992), Kendon (2004), and Bressem, Ladewig, and Müller (2013). From the analysis of the texts, it was observed that disfluency phenomena tend to occur not only in the prosodic domain but also in the gestural domain. Rhetorical scansions have their prosodic emphases coinciding with the points of greatest energy in gestural production. In multiple comments, the strong connection between them and the type of relationship established prosodically and semantically also appears to manifest in the gestural sphere. In topics, there is a coincidence between the presence of prosodic focus and the presence of strokes. Longer locutive introducers may coincide with a greater number of gestural phases.